Kemampuan Membaca Memahami Teks Dongeng Bahasa Jerman - Chaidir, Muh. Ilham Alfadil; Usman, Misnawaty (Universitas Negeri Makassar, 2025)
Abstract. This research aims to determine the level of reading comprehension of German fairy tale texts by students of SMA Islam Athirah Bukit Baruga. This research uses a quantitative descriptive method which consists of 4 question types, each of which contains 10 questions. The question types are multiple choice questions, matching questions, fill-in-the-blank questions and true-false questions. The population of this research was the students of class XII of SMA Islam Athirah Bukit Baruga who programmed German as a subject, a total of 26 students. In this research, the method of total sampling is used, i.e. the sample is considered as a whole. The results of this research indicate that the ability to understand German fairy tale texts among the students of SMA Islam Athirah Bukit Baruga in the multiple choice tests is in the category